Regional security in the Middle East past, present, and future - Maoz, Zeev (Frank Cass, 1997)
Middle Eastern politics of the 1990s have been characterized by a drive towards peace, the success of which will depend on the negotiating process. This volume discuss the challenges, and provide some practical advice on how to avoid failure.